Electron- and photon-impact atomic ionisation - Bray, Igor; Fursa, Dmitry; Kadyrov, Alisher; Stelbovics, Andris; Kheifets, A.; Mukhamedzhanov, A. (Elsevier, 2012)
The past decade has seen extraordinary theoretical progress in the field of fully kinematically resolved atomic electron-impact ionisation, and its closely related field of double photoionisation. These processes were challenging to calculate due to formal and computational difficulties associated with break-up problems involving the long-range Coulomb potential. Presently, however, these processes can be calculated accurately for simple targets such as atomic hydrogen and helium, irrespective of the kinematics considered or the geometry of detectors. We report on the computational progress, and how it has resulted in a deeper understanding of the formalism of Coulomb few-body problems.